On the Use of Mist Nets for Population Studies of Birds - MacArthur, Robert H. (1974)
Studies in which birds are captured in mist nets, marked, and released can yield much more information than previously realized. When nets are erected, the capture rate is initially high and then decreases with time, as more and more of the resident bird individuals in the vicinity are captured and learn to avoid the nets a second time. The capture rate eventually reaches an asymptotic value depending on the number of “drifting,” nonresident individuals in the vicinity. We describe a simple theoretical formulation of this decline in capture rate, and we show how it can be used to estimate the sizes of the resident population and the drifting population separately. To illustrate the theory, we apply it to the results of a netting study in a Vermont forest. Variation among species in capture efficiency is correlated in part with preferred vertical foraging position. Species may be characterized as “smart” or “dumb” by the criterion of relative recapture frequency.